Critical uncoupling between biogeochemical stocks and rates in Ross Sea springtime production–export dynamics - M. G. Meyer; M. G. Meyer; E. Portela; E. Portela; W. O. Smith Jr.; W. O. Smith Jr.; K. J. Heywood (Ocean Science)
Three biogeochemical glider surveys in the Ross Sea between 2010 and 2023 were combined and analysed to assess production–export stock and rate dynamics. As the most productive of any Antarctic continental shelf, the Ross Sea is a site of substantial physical and biogeochemical interest. While this region and its annual bloom have been characterised for decades, logistical constraints, such as ship time and sea ice cover, have prevented a comprehensive understanding of this region over long (> 1–2 months) timescales and at high spatiotemporal resolution. Here, we use high-resolution datasets from autonomous gliders in mass balance equations to calculate short-term (days to weeks) net community production via oxygen concentration, change in particulate organic carbon (POC) concentration over time, and POC export potential during the period of peak primary production in the region (November–February). Our results show an overall decoupling of net community production (NCP), driven by biologic changes in oxygen, from overall biomass concentration as well as changes in POC over time. NCP and carbon change vary between seasons and appear related to changes in ice concentration and stratification. Substantial spatiotemporal variability exists in all datasets, but high-resolution sampling reveals short-term variations that are likely masked in other studies. Our study reinforces the need for high-resolution sampling and supports previous classifications of the Ross Sea as a high-productivity (average NCP range −0.7 to 0.2 g C m−2 d−1), low-export (average changes in POC over time range −0.1 to 0.1 g C m−2 d−1) system during the productive austral spring and sheds additional light on the mechanisms controlling these processes.